Efektivitas Buku Digital terhadap Empati Siswa Kelas IV SDN Bugangan 01 Semarang - Zumala, Fata; Purnamasari, Veryliana; Siti Badriyah; Agustini, Ferina (Indo-MathEdu Intellectuals Journal, 2024)
Education plays an important role in producing a superior and characterful young generation, so it is necessary to instill empathy in students. This study aims to determine the effectiveness of digital books on empathy in grade IV students of SDN Bugangan 01. This study uses quantitative research with a pre-experimental design, with a one group pretest-posttest design. The population in this study was grade IV, totaling 22 students. Research data were collected through a questionnaire in the form of a checklist of 25 questions to measure the level of student empathy. Data processing in this study used a normality test, homogeneity test, paired sample t-test and N-Gain test. The results of the pretest normality test have a significance value of 0.251 > 0.05, while the posttest value is 0.175 > 0.05. Then in the homogeneity test the significance is 0.224 > 0.05. This shows that the data is normally distributed and homogeneous. The results of the paired sample t-test show that digital books are effective in empathy in grade IV students. Furthermore, the N-Gain test shows a value of 0.51. So, digital books are effective for the empathy of grade IV students at SDN Bugangan 01 which is classified as moderate